The Influence of Digital Tax Literacy, Trust in E-Tax System, Religiosity, and Nationalism on Tax Compliance of Individual Taxpayers at KPP Pratama Kediri - Diana Fitria Hermanita; Imroatus Suaida; Eni Srihastuti (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This research is motivated by the transformation of digital-based tax administration that requires digital tax literacy and trust in the e-tax system, and is influenced by the values of religiosity and nationalism in shaping tax compliance. This study aims to analyze the influence of Digital Tax Literacy, Trust in E-tax System, Religiosity, and Nationalism on the Tax Compliance of Individual Taxpayers at KPP Pratama Kediri. The research method used was quantitative with an associative design through a survey of 51 Individual Taxpayers using a four-level Likert scale questionnaire. Data were analyzed using simple linear regression and multiple linear regression at a significance level of 5%. The results of the study show that partially Digital Tax Literacy has an effect of 16,6%, Trust in E-tax System by 18,6%, Religiosity by 15,2%, and Nationalism by 38,6% on Tax Compliance. Simultaneously, the four variables were able to explain 45,9% of the variation in Tax Compliance and had a statistically significant effect. The novelty of this research lies in the integration of technological factors, institutional trust, and moral and civic values in an empirical model of tax compliance for Individual Taxpayers in the digital era.